Associations between benign paroxysmal positional vertigo and seven mental disorders: a two-sample Mendelian randomization study - Liu, Shihan; Zhang, Lingli; Deng, Dan; Luo, Wenlong (Frontiers in Neurology, 2024)
The association between benign paroxysmal positional vertigo (BPPV) and various mental disorders is still controversial. In this study, the Mendelian randomization (MR) method was used to clarify the correlation between BPPV and seven mental disorders (bipolar disorder, depression, anxiety disorder, schizophrenia, suicidality, neuroticism, and mood swings) to aid in the exploration of BPPV complications and the prevention and early treatment of mental disorders.The datasets for BPPV and seven mental disorders were obtained from genome-wide association studies (GWAS). Two-sample MR was used to analyse the correlation between exposure (BPPV) and various outcomes (bipolar disorder, depression, anxiety disorder, schizophrenia, suicidality, neuroticism, and mood swings). A reverse MR study was also performed. The inverse variance weighting (IVW) method, MR -Egger method, simple mode method, weighted mode method, and weighted median method were selected.The MR analysis results did not reveal significant associations between BPPV and bipolar disorder, depression, anxiety disorder, schizophrenia, suicidal tendencies, neuroticism, and mood swings. No significant associations were found in the reverse MR analysis for bipolar disorder, depression, anxiety disorder, schizophrenia , or suicidal tendencies with BPPV. Interestingly, neuroticism (IVW: OR = 1.142, 95% CI:1.059-1.231, P = 0.001; P-MR-PRESSON adjustment = 0.0002) and mood swings (IVW: OR = 3.119, 95% CI: 1.652-5.884, P = 0.0004) may have a significant association with BPPV. After MR-PRESSON adjustment, there was no horizontal pleiotropy or heterogeneity, and it still suggests a significant association between neuroticism, mood swings, and BPPV.We conducted MR analysis on genetic data from European populations and discovered a causal relationship between BPPV and seven mental disorders. Our research findings suggest that BPPV may not have a significant causal relationship with bipolar disorder, depression, anxiety disorder, schizophrenia, or suicidal tendencies. However, neuroticism and mood swings may be risk factors for BPPV.